A Case of Cystic Dysplasia of the Rete Testis in a 17-Months-Old Boy. (3rd July 2011) - Poupalou, Anna; Spyridis, George; Vakaki, Marina; Giamarelou, Panagiota; Petousis, George; Nikolaidis, Pantelis
Abstract : Cystic dysplasia of the testis (CDT) is a benign, congenital malformation of the testis and a rare cause of painless scrotal swelling in children, mimicking testicular cancer. It is commonly unilateral, often associated with ipsilateral wolffian duct and ureteral abnormalities. Cystic dysplasia of the rete testis (CDT) represents a diagnostic challenge made easier if age, precise localisation, typical ultrasonographic features, the presence or absence of associated genitourinary malformations, as well as tumor markers are considered. The definite treatment of such a benign lesion is testis-sparing surgery, however in most cases watch and wait strategy can be recommended. We present a case of cystic dysplasia of the testis in a 17-month-old boy with right multicystic dysplastic kidney, epididymal cyst, history of vesicoureteral reflux (VUR), as well as of solitary umbilical artery. We performed epididymidal cyst enucleation and right testicular biopsy.